Emotional Intelligence in Malaysian Police: A Review - Kanesan, Pavitra (UNIMAS Publisher, 2019)
This article discussed the findings of previous studies on emotional intelligence in Royal Malaysia Police. Based on the review, emotional intelligence related to job stress, job satisfaction, job commitment, work-life balance, and psychological well-being of police officers. Review concludes that no significant differences in emotional intelligence by demographic factors like salary, working department, age, marital status, length of service, and job position. Police department has to organise training and seminars to enhance the emotional intelligence level of police officers. More studies have to be done on emotional intelligence in the police department, thus the findings will be helpful for the organisation’s development.